Sanskrit and Pāli Influence on Languages and Literatures of Ancient Java and Burma - Zakharyin, Boris (Lingua Posnaniensis, 2013)
This paper describes the linguistic and cultural influence of India on the countries of Indo-China in the 5th to 15th centuries A D. It is shown that India’s penetration into South-East Asia took the forms of Late Brahmanism Early Hinduism and of Buddhism. Indian settlers were promoting different variants of Sanskrit written culture in Java. Differences between culturally dominant Sanskrit, the language of the Indian migrants, and the orally used Austronesian languages of Java were great; as a result of interaction between the two there appeared highly Sanskritized versions of Old Western Javanese (Kavi) and later also of Old Balinese. Between the 7th and 15th centuries a great number of literary texts in Kavi were created in Java. The influx of Indian culture into ancient Burma, realized mostly by the land-route and only partially by sea, implied two main waves differing linguistically: the Sanskrit-bound wave and the P āli-bound one. Under the influence of Sanskrit and numerous texts in Sanskrit a Mon script based on the Indian brāhmī was developed in Upper Burma in the 9th century; later on it became the national system of writing, in use even today. The starting point for the history of Pāli epigraphy and literature in Burma was 1058 AD when Theravāda Buddhism was proclaimed the state religion of the Pagan kingdom. In the 11th to 15th centuries a great number of works in different fields of knowledge appeared in Burma. T he language used in them was a creolized Pāli/Burmese resulting from the intensive linguistic interaction between Pāli and Sanskrit on one hand and the vernaculars on the other. The most important stages in the development of this language and of literary activity in it are characterized.